Family as a Social Influence Manager in Determining the Lifestyle of Students in the Campus Environment - Maunah, Binti; Komsiyah, Indah (Didaktika Religia, 2023)
The objective of this article is to examine the role of the family in shaping student lifestyle on the campuses of UIN Sunan Kalijaga Yogyakarta, UIN Sayyid Ali Rahmatullah Tulungagung, and IAIN Kediri. The methodological perspective adopted was that of qualitative field research with a multi-case study approach. In order to collect data, in-depth interviews, participatory observation and documentation were conducted. This article concludes that the family exerts a significant influence on the lifestyle patterns of students on the three campuses. The family exerts considerable influence over the lifestyle choices of students within the campus environment. The values, habits and beliefs instilled by the family during childhood have a profound impact on the lifestyle of students. Additionally, the lifestyles of students are influenced by the habits of their immediate environment. Several challenges were identified in regulating student lifestyles. The campus has implemented effective solutions to ensure that student lifestyles adhere to ethical standards.